The Spectrum of Thyroid Dysfunction During Pregnancy and Fetomaternal Outcome, A Study from the Premier Institute of Western India - Ranesh Debbarma; Meenakshi Gothwal; Pratibha Singh; Garima Yadav; Purvi Purohit; Navdeep Kaur Ghuman; Neeraj Gupta (Wolters Kluwer Medknow Publications, 2024)
Background: Thyroid dysfunction evaluation during pregnancy is important for the mother's health, obstetric outcomes, and the child's cognitive development. This study is conducted to know various thyroid disorders that can occur during antenatal and their impact on mother and fetus outcomes. Materials and Methods: This observational research was conducted over two years at a tertiary center in Western Rajasthan, India. Seven hundred and seventy-two low-risk singleton pregnant patients who met the inclusive criteria were recruited. The estimation of T3, T4, and TSH was done along with a routine investigation in antenatal women. Antenatal having abnormal thyroid profiles were then analyzed for mother and fetus problems. Results: The prevalence of thyroid dysfunction in antenatal women is 16.5%. Subclinical hypothyroidism (SCH) was seen in 12.5% of cases, overt hypothyroidism in 3.36%, and subclinical hyperthyroidism in only 0.51% of cases. Anti-TPO was positive in 46 (41.44%) women with hypothyroidism and 1 (25%) with hyperthyroidism. Compared to euthyroid women, women with overt hypothyroid (19.23% vs 3.1%, P = 0.002) and subclinical hypothyroid (9.27% vs 3.1%, P = 0.003) were found to be associated with a higher risk of hypertensive disease. Concerning fetal outcomes. There was a high risk for preterm (12.37% v/s 4.9%, P = 0.004) and fetal growth retardation (FGR) in patients with SCH (7.21% v/s 3.1%, P = 0.04). Conclusion: Considering the significant influence of thyroid disorders on mother and fetus outcomes, the screening for thyroid during pregnancy should be considered universally, particularly in developing countries with high prevalent rates, such as India.